Merdeka Curriculum for Preventing Low Back Pain in School-aged Children - Nababan, Nelly Herawaty; Puspitasari, Putri; Jaladara, Vena (BKM Public Health and Community Medicine, 2024)
Purpose: Adolescence is a crucial phase marked by swift growth and progress, where adolescents might encounter musculoskeletal problems like LBP. Several factors, such as bad posture, heavy backpacks, inactive routines, and sports involvement, play a role in the development of LBP. These can affect future health and quality of life, given that school-aged children are crucial periods for physical development and puberty. This abstract highlights the factors contributing to LBP in adolescents and provides recommendations for prevention and management, including integrating occupational health and safety (OHS) topics into the Merdeka Curriculum, to address LBP prevention in schools. Content: This initiative focuses on integrating health topics into the Merdeka Curriculum to educate students on preventing LBP. The current Merdeka Curriculum includes health teaching materials such as nutrition, sanitation, mental health, and physical activity. However, OHS materials for schools have not been developed. The availability of OHS topics related to proper posture and preventing sedentary lifestyles through comics, posters, and videos will attract students' interest. Given that the Merdeka curriculum emphasises student-centred learning, practices such as safety talk, classroom stretching exercises, outdoor activity, and screen-free periods at school could potentially be effective in introducing OHS. The main challenge of this solution is the incomplete adoption of the curriculum across all schools. Other possible solutions include providing lockers and health promotion by health professionals. Preventing and controlling LBP in school-aged children necessitates a comprehensive strategy that tackles their lifestyle choices, surroundings, and availability of medical services. Through the introduction of educational, advocacy for ergonomic practices, promotion of regular physical exercise, regulation of screen usage, and guaranteeing healthcare accessibility, we can alleviate the impact of LBP on adolescents and enhance their general well-being.